Epidemiology of physical–mental multimorbidity and its impact among Aboriginal and Torres Strait Islander in Australia: a cross-sectional analysis of a nationally representative sample. Issue 10 (11th October 2022) - Carman, William; Ishida, Marie; Trounson, Justin S; Mercer, Stewart W; Anindya, Kanya; Sum, Grace; Armstrong, Gregory; Oldenburg, Brian; McPake, Barbara; Lee, John Tayu
Abstract : Objectives: This study aimed to examine the differences in multimorbidity between Aboriginal and Torres Strait Islander people and non-Indigenous Australians, and the effect of multimorbidity on health service use and work productivity. Setting: Cross-sectional sample of the Household, Income and Labour Dynamics in Australia wave 17. Participants: A nationally representative sample of 16 749 respondents aged 18 years and above. Outcome measures: Multimorbidity prevalence and pattern, self-reported health, health service use and employment productivity by Indigenous status. Results: Aboriginal respondents reported a higher prevalence of multimorbidity (24.2%) compared with non-Indigenous Australians (20.7%), and the prevalence of mental–physical multimorbidity was almost twice as high (16.1% vs 8.1%). Multimorbidity pattern varies significantly among the Aboriginal and non-Indigenous Australians. Multimorbidity was associated with higher health service use (any overnight admission: adjusted OR=1.52, 95% CI=1.46 to 1.58), reduced employment productivity (days of sick leave: coefficient=0.25, 95% CI=0.19 to 0.31) and lower perceived health status (SF6D score: coefficient=−0.04, 95% CI=−0.05 to −0.04). These associations were found to be comparable in both Aboriginal and non-Indigenous populations. Conclusions: Multimorbidity prevalence was significantly greater among Aboriginal and Torres Strait Islanders compared with the non-Indigenous population, especially mental–physical multimorbidity. Strategies are required for better prevention and management of multimorbidity for the aboriginal population to reduce health inequalities in Australia.